2019
DOI: 10.3389/fphar.2019.00503
|View full text |Cite
|
Sign up to set email alerts
|

Artocarpus tonkinensis Protects Mice Against Collagen-Induced Arthritis and Decreases Th17 Cell Function

Abstract: Artocarpus tonkinensis (Moraceae) is a tree that grows in north Vietnam whose leaf decoction is used as a traditional remedy by the Hmong ethnic group to treat arthritis and backache. Our study evaluated the decoction's efficacy and mechanism of action in DBA/1J mice with collagen-induced arthritis (CIA). Mice treated with the decoction (At) either from the first collagen immunization or after CIA development experienced significantly less joint edema and inflammatory infiltration, whereas CIA-induced cartilag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…At water extract fingerprint included catechin, alphitonin-4-O-β-D-glucoside (TAT-6), maesopsin-4-O-β-D-glucoside (TAT-2) (Supplementary Figure S1), quercetin-3-β-D-glucoside, kaempferol-3-O-glucoside, quercetin, kaempferol. Concentrations of the most abundant compounds, TAT-6 and TAT-2, were 142.8 µg/ml and 122.5 µg/ ml, respectively (Adorisio et al, 2019). The very same batch of At (No.…”
Section: A Tonkiniensis Water Extractmentioning
confidence: 92%
See 4 more Smart Citations
“…At water extract fingerprint included catechin, alphitonin-4-O-β-D-glucoside (TAT-6), maesopsin-4-O-β-D-glucoside (TAT-2) (Supplementary Figure S1), quercetin-3-β-D-glucoside, kaempferol-3-O-glucoside, quercetin, kaempferol. Concentrations of the most abundant compounds, TAT-6 and TAT-2, were 142.8 µg/ml and 122.5 µg/ ml, respectively (Adorisio et al, 2019). The very same batch of At (No.…”
Section: A Tonkiniensis Water Extractmentioning
confidence: 92%
“…Previous studies by Adorisio et al (Adorisio et al, 2019) demonstrated the immunoregulatory activity of A. tonkinensis water extract in CIA mouse model. A. tonkinensis decoction limited CIA progression when it was administered after arthritis development and prevented CIA if it was given before appearance of clinical signs.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations